Androgen receptor-reduced sensitivity is associated with increased mortality and poorer glycaemia in men with type 2 diabetes mellitus: a prospective cohort study. Issue 1 (18th August 2020) - Heald, Adrian H.; Yadegar far, Ghasem; Livingston, Mark; Fachim, Helene; Lunt, Mark; Narayanan, Ram Prakash; Siddals, Kirk; Moreno, Gabriela; Jones, Richard; Malipatil, Nagaraj; Rutter, Martin; Gibson, Martin; et al.
Abstract : Introduction: Hypogonadism is associated with poorer glycaemic outcomes/increased all-cause and cardiovascular morbidity/mortality in type 2 diabetes mellitus (T2DM). Increasing CAG repeat number within exon-1 of the androgen receptor (AR) gene is associated with increased AR resistance/insulin resistance. Methods: We determined in a long-term 14-year follow-up cohort of 423 T2DM Caucasian men, the association between baseline androgen status/CAG repeat number (by PCR then Sequenom sequencing) and metabolic/cardiovascular outcomes. Results: Metabolic outcomes : Lower total testosterone was associated with higher BMI (kg/m 2 ) at 14-year-follow-up: regression coefficient −0.30 (95% confidence interval −0.445 to −0.157), P = 0.0001. The range of CAG repeat number was 9-29 repeats. Higher CAG repeat number in exon-1 of the AR gene was associated with higher follow-up HbA1c2016 – each unit increase in CAG repeat-associated with an increment of 0.1% in HbA1C2016 ( P = 0.04), independent of baseline testosterone. Cardiovascular outcomes and mortality : At an average of 14-year-follow-up, 55.8% of hypogonadal men had died vs 36.1% of eugonadal men ( P = 0.001). There was a 'u' shaped relation between number of CAG repeats and mortality. Twenty-one CAG repeats were associated with an up to nearly 50% lower mortality rate than <21 CAG repeats and >21 CAG repeats – independent of baseline testosterone level. Conclusion: A higher number of CAG repeats at the AR gene associates with higher future HbA1c. There was a 'u' shaped relation between CAG repeat number and mortality rate. Determination of CAG repeat number may become part of assessment of androgen status/its consequences for men with T2DM.